Morphological processing in the flankers task. Issue 3 (2nd April 2021) - Grainger, Jonathan; Snell, Joshua; Beyersmann, Elisabeth
ABSTRACT: Does the processing of words with a transparent morphological structure benefit from this structure? Here we show that the flankers task provides an interesting novel angle on this well-researched issue. Participants saw transparent suffixed target words flanked by their stem (e.g. farm farmer farm ), as well as pseudo-suffixed words and non-suffixed words flanked by their embedded word (e.g. corn corner corn ; cash cashew cash ). Targets were also tested with unrelated word flankers (e.g. book farmer book ), and participants made lexical decisions to the central targets. We predicted that truly suffixed word identification would be facilitated by the presence of stem flankers over and above any purely orthographic effects that were expected to be revealed in the pseudo-morphological and non-morphological conditions. We found exactly that pattern and conclude that parallel processing of distinct word identities in the flankers task is modulated by the transparent morphological relations between these words.